The Relationship Between Physical Activity And Sleep Quality Among Nurses In Hospitals - Bela, Widia Cyntia; Pramana, Yoga; Rahmawati, Nadia; Fauzan, Suhaimi; Maulana, Muhammad Ali (ProNers, 2024)
Background: Sleep quality is essential for maintaining physical and mental health. Nurses often face challenges in achieving good sleep quality due to demanding work schedules, high physical activity levels, and irregular shifts, which can lead to poor sleep and reduced overall well-being.Objective: To examine the relationship between physical activity levels and sleep quality among nurses at Bhayangkara Pontianak Hospital.Methods: This study employed a quantitative cross-sectional design. A total of 73 nurses were included using a total sampling technique. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality and the International Physical Activity Questionnaire (IPAQ) to measure physical activity levels. The data were analyzed using Spearman Rank correlation.Results: The findings showed a weak negative correlation between physical activity and sleep quality, indicating that higher physical activity levels were associated with poorer sleep quality. Nurses with high physical activity levels and night shift schedules were more likely to experience sleep disturbances. External factors such as environmental conditions and work-related stress also contributed to sleep quality issues.Conclusion: Physical activity has a significant impact on sleep quality among nurses. High physical activity levels, coupled with demanding workloads and irregular shifts, can impair sleep quality. It is recommended that institutions implement strategies to balance physical activity and rest, improve work schedules, and provide support systems to enhance nurses"™ well-being.